Economics of milkfish farming in selected barangays of the municipality of Panay, Capiz - Casimero, Ian Jude Villmaor (1999.)
This study tells about the socio-economic characteristics of fishfarmers such as income, educational attainment, age, sex, civil status, family size, etc. and the costs and returns incurred by the fishfarmers in milkfish farming., It was found out that income educational attainment and experiences of fishfarmers are the main socio-economic characteristics that affected the milkfish culture. The results obtained that milkfish farming in selected barangays of Panay, Capiz was profitable. The respondents from Barangay pawa yielded more profit compared to the Barangays that was studied. One hundred percent of the fishfarmers in Panay practiced semi-intensive method of milkfish farming. The main problem of most of the respondents was the unstable price structure. This was influenced by the shifting of prawn farmers into milkfish culture thereby increasing the supply of milkfish in the market.
Research Project (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Milkfish Farming